E-commerce in BRICS Countries - Svetlana A. GUSAROVA; Igor V. GUSAROV; Margarita S. SMERETCHINSKII (Communications of International Proceedings, 2022)
Almost every country in the world faced the devastating effects of the pandemic, led to a significant reduction in their economic development. In an effort to cope with the emerging problems, the BRICS countries (Brazil, Russia, India, China, and South Africa) help each other by expanding Intra-group economic cooperation. One of innovative form of their interaction is the development of e-commerce on the base of the BRICS Strategy for Economic Partnership. The relevance of the study is due to the fact that e-commerce is a growth driver for the economies of developing countries, including the BRICS countries. The paper concluded that China is the world's largest e-commerce market. It was revealed the Internet of Things, cloud computing, etc., contribute to the growth of this economic sphere. It is noted that despite the fact that Russia has the largest number of Internet users in Europe, the volume of e-commerce in the country is small. The conclusion is made about the prospects for further development of electronic commerce in the BRICS countries, about the importance of stimulating this process. As a result of the study, the advantages and bottlenecks of e-commerce, as well as the main directions of its development in the BRICS countries, were identified.
Keywords: E-commerce; China; BRICS cooperation